2021
DOI: 10.3390/sports9070088
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Approach to 1RM Prediction Using the Load-Velocity Profile: A Comparison of Models

Abstract: The study aim was to compare different predictive models in one repetition maximum (1RM) estimation from load-velocity profile (LVP) data. Fourteen strength-trained men underwent initial 1RMs in the free-weight back squat, followed by two LVPs, over three sessions. Profiles were constructed via a combined method (jump squat (0 load, 30–60% 1RM) + back squat (70–100% 1RM)) or back squat only (0 load, 30–100% 1RM) in 10% increments. Quadratic and linear regression modeling was applied to the data to estimate 80%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
29
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(32 citation statements)
references
References 41 publications
1
29
2
Order By: Relevance
“…The absence of a maximal effort cue in the present study, by design, provides a meaningful comparison with another recent study that did utilize the maximal effort cue with well-trained males in the back squat. Thompson and colleagues (2021) found that a mixed exercise (jump squats and back squats) quadratic prediction equation was able to predict 1RM value within ±3kg , further supporting that providing a maximal intended velocity cue may be necessary for submaximal velocity to accurately predict 1RM value in various exercises (Thompson et al, 2021).…”
Section: Discussionmentioning
confidence: 95%
“…The absence of a maximal effort cue in the present study, by design, provides a meaningful comparison with another recent study that did utilize the maximal effort cue with well-trained males in the back squat. Thompson and colleagues (2021) found that a mixed exercise (jump squats and back squats) quadratic prediction equation was able to predict 1RM value within ±3kg , further supporting that providing a maximal intended velocity cue may be necessary for submaximal velocity to accurately predict 1RM value in various exercises (Thompson et al, 2021).…”
Section: Discussionmentioning
confidence: 95%
“…The grouped effect sizes for magnitude of difference between predicted and actual 1RM are presented graphically in Fig 2 . Twenty studies (80%) included male participants only [ 6 , 9 , 15 , 17 19 , 28 41 ], three studies (12%) feature both male and female participants [ 12 , 13 , 42 ], one study (4%) included only females participants [ 43 ] and one study (4%) did not describe the sex of participants [ 44 ]. The training experience of participants also varied substantially across each of the studies included.…”
Section: Resultsmentioning
confidence: 99%
“…Caven and associates reported larger effect sizes using 2-load predictions of bench press (ES = 0.32 to 0.33) and squat (ES = 0.23 to 0.29) 1RM when compared to a model using 8-loads (bench press ES = 0.10 to 0.11; squat ES = 0.16 to 0.19) [ 43 ]. The remaining studies highlighted no differences between predictions performed using 2- vs. 4-load [ 30 , 31 , 40 , 42 ], 2- vs. 5-load [ 18 , 19 ], 2- vs. 7-load [ 39 ], 4- vs. 7-load [ 41 ], 4- vs. 7-load [ 36 ], 2- vs. 3- vs. 4-load [ 12 ], or 3- vs.4- vs. 5-load models [ 34 ]. Despite minimal evidence that validity differs between models, the mean grouped effect size appears to increase (i.e., poorer validity) when a greater number of loads are used.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations